Leaves of grass, 1860 : the 150th anniversary facsimile edition - Whitman, Walt, 1819-1892 (Iowa Whitman series., 2009)
In May 1860, Walt Whitman published a third edition of Leaves of Grass. His timing was compelling. Printed during a period of regional, ideological, and political divisions, written by a poet intimately concerned with the idea of a United States as "essentially the greatest poem," this new edition was Whitman's last best hope for national salvation. Now available in a facsimile edition, Leaves of Grass, 1860 faithfully reproduces Whitman's attempt to create a "Great construction of the New Bible" to save the nation on the eve of civil war and, for the first time, frames the book in historical.